2024
DOI: 10.1039/d3tc04511k
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquid-assisted growth of high-quality methylammonium lead bromide single crystals for photodetection applications

Apurba Mahapatra,
Vishnu Anilkumar,
Joanna Kruszyńska
et al.

Abstract: The control of nucleation temperature and growth kinetic during the inverse temperature crystallization (ITC) method is critical to achieve high quality perovskite single crystals (SCs) for various optoelectronic application. Here...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…To assess the electrical properties of MHPSCs, a thorough understanding of their electro-ionic interaction phenomena is crucial. This has been a focal point in the perovskite community, and attempts to understand these phenomena have been made by using current–voltage ( J – V ), current–transient ( I – T ), and electrochemical impedance spectroscopy (EIS) measurements under the conditions of varied temperatures, scan rates, or biases. In comparison to J – V and I – T studies, EIS has emerged as a robust characterization tool due to its ability to provide information related to the ionic and charge movements with variation in frequency …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the electrical properties of MHPSCs, a thorough understanding of their electro-ionic interaction phenomena is crucial. This has been a focal point in the perovskite community, and attempts to understand these phenomena have been made by using current–voltage ( J – V ), current–transient ( I – T ), and electrochemical impedance spectroscopy (EIS) measurements under the conditions of varied temperatures, scan rates, or biases. In comparison to J – V and I – T studies, EIS has emerged as a robust characterization tool due to its ability to provide information related to the ionic and charge movements with variation in frequency …”
Section: Introductionmentioning
confidence: 99%
“…However, practically, it has been found that the identified ECs often fail to provide an accurate classification of the EIS in varying stimuli conditions such as bias, temperature, and intensity. , One such method to identify the circuit type based on a human-learned approach was introduced by Huang et al, where they tried to correlate the impedance shape and the electrocatalytic activity, where a systematic mathematical analysis of first single-adsorbate reactions and subsequently more sophisticated reactions involving multiple adsorbates was utilized . Previously, we also discussed the evolution of EIS with respect to changes in the applied bias, temperature, and wavelength for perovskite solar cells and SCs. , , In such situations, a close watch on the evaluation of EIS spectra, along with the identification of the appropriate EC, is crucial and needs to be performed precisely. Second, the extraction of circuit parameters within an acceptable range of accuracy is another crucial aspect.…”
Section: Introductionmentioning
confidence: 99%